Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

A spinel-structured coat layer on lithium transition metal composite oxides addresses Li ion conductivity and Mn elution issues, enhancing the rate and cycle performance of secondary batteries.

JP7624604B2Active Publication Date: 2025-01-31PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021551284
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-29
Publication Date
2025-01-31
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

Existing lithium transition metal composite oxides with spinel structures face issues of reduced Li ion conductivity and potential Mn elution leading to deteriorated battery characteristics, particularly in high-rate secondary batteries.

Method used

A coat layer with a spinel structure, containing Li and excluding Mn, is formed on the surface of lithium transition metal composite oxides to maintain Li ion conductivity and stabilize the surface structure, thereby improving rate characteristics and cycle maintenance.

Benefits of technology

The coat layer enhances Li ion conductivity and prevents Mn elution, resulting in improved rate characteristics and cycle maintenance of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624604000002
    Figure 0007624604000002
  • Figure 0007624604000001
    Figure 0007624604000001
Patent Text Reader

Abstract

A positive electrode active material for nonaqueous electrolyte secondary batteries according to the present invention comprises: a lithium transition metal composite oxide which has a spinel structure; and a coating layer which is provided on the surface of the lithium transition metal composite oxide, while having a spinel structure, and which contains Li but does not contain Mn.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery using the positive electrode active material. [Background technology]

[0002] Lithium transition metal composite oxides containing Li, Ni, and Mn and having a spinel structure have attracted attention as positive electrode active materials because of their high battery potential and abundant recoverable reserves of Mn. Patent Document 1 discloses a positive electrode active material in which the surface of a lithium manganese oxide is coated with a lithium-free oxide having a spinel structure in order to prevent deterioration of battery characteristics under high temperature and high voltage conditions. Patent Document 2 discloses a positive electrode active material made of a lithium manganese oxide having a spinel structure and a two-layer structure with different compositions on the surface and inside in order to prevent deterioration of battery characteristics. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-234818 A [Patent Document 2] Special Publication No. 2008-535173 Summary of the Invention

[0004] The positive electrode active material disclosed in Patent Document 1 has a coating of a lithium-free oxide, so that Li ion conductivity decreases, and battery characteristics such as rate characteristics and battery capacity may deteriorate. In addition, the positive electrode active material disclosed in Patent Document 2 contains Mn on the surface, so that Mn may dissolve and deteriorate the battery characteristics. On the other hand, the positive electrode active materials disclosed in Patent Document 1 and Patent Document 2 are ones that suppress the deterioration of the positive electrode active material by coating, and have not been considered from the viewpoint of improving the battery characteristics, so there is still room for improvement. In addition, in recent years, high-rate secondary batteries have been required, and there is a demand for improving the rate characteristics.

[0005] A positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a lithium transition metal composite oxide having a spinel structure, and a coating layer having a spinel structure, which contains Li and does not contain Mn and is provided on a surface of the lithium transition metal composite oxide.

[0006] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode containing the above-described positive electrode active material for nonaqueous electrolyte secondary batteries, a negative electrode, and an electrolyte.

[0007] According to one aspect of the present disclosure, by forming a predetermined coating layer on the surface of a lithium transition metal composite oxide, the rate characteristics of a secondary battery can be improved. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a perspective view of a secondary battery according to an embodiment, showing the internal structure of a battery case with the front side of an exterior body removed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Lithium transition metal composite oxides containing Li, Ni, and Mn and having a spinel structure have a high battery potential, but the Mn on the surface 3+ Mn due to disproportionation 2+There is a problem that the elution of Li occurs and the surface structure becomes unstable. Patent Document 1 and Patent Document 2 disclose a technique of preventing deterioration of battery characteristics by coating the surface of lithium manganese oxide, but the technology is not considered from the viewpoint of actively improving battery characteristics by coating. The inventors of the present application have found that a secondary battery with improved rate characteristics can be obtained by providing a coating layer having a spinel structure containing Li and not containing Mn on the surface of a lithium transition metal composite oxide containing Li, Ni, and Mn and having a spinel structure. This is presumably because the inclusion of Li in the coating layer maintains Li ion conductivity, while the absence of Mn makes it possible to suppress destabilization of the spinel structure due to the elution of Mn. Furthermore, as described below, it has been found that the cycle retention rate can be improved while improving the rate characteristics by setting the molar fraction of the metal elements other than Li contained in the coating layer to 0.1% to 5% with respect to the total molar number of the metal elements other than Li contained in the lithium transition metal composite oxide.

[0010] An example of an embodiment of the present disclosure will be described in detail below. In this embodiment, a secondary battery 100 including a rectangular metal exterior body 1 is illustrated, but the exterior body is not limited to a rectangular shape and may be, for example, cylindrical. In addition, a wound electrode body 3 is illustrated, but a laminated electrode body in which multiple positive electrodes and multiple negative electrodes are alternately laminated one by one with separators interposed therebetween may also be used. In addition, in both the positive and negative electrodes, a case in which each composite layer is formed on both sides of each core body is illustrated, but each composite layer is not limited to being formed on both sides of each core body, and may be formed on at least one surface.

[0011] 1, the secondary battery 100 includes a wound electrode assembly 3 formed in a flat shape having a flat portion and a pair of curved portions by winding a positive electrode and a negative electrode with a separator interposed therebetween, an electrolyte, and an exterior body 1 that contains the electrode assembly 3 and the electrolyte. Both the exterior body 1 and the sealing plate 2 are made of metal, and are preferably made of aluminum or an aluminum alloy.

[0012] The exterior body 1 has a bottom part that is generally rectangular in bottom view, and side walls that stand on the periphery of the bottom part. The side walls are formed perpendicular to the bottom part. The dimensions of the exterior body 1 are not particularly limited, but an example is a lateral length of 60 to 160 mm, a height of 60 to 100 mm, and a thickness of 10 to 40 mm.

[0013] The positive electrode is a long body having a metallic positive electrode core and a positive electrode composite layer formed on both sides of the core, and a strip-shaped positive electrode core exposed portion 4 is formed at one end in the short direction, where the positive electrode core is exposed along the longitudinal direction. Similarly, the negative electrode is a long body having a metallic negative electrode core and a negative electrode composite layer formed on both sides of the core, and a strip-shaped negative electrode core exposed portion 5 is formed at one end in the short direction, where the negative electrode core is exposed along the longitudinal direction. The electrode body 3 has a structure in which the positive electrode and negative electrode are wound with a separator interposed between them, with the positive electrode core exposed portion 4 of the positive electrode arranged at one axial end and the negative electrode core exposed portion 5 of the negative electrode arranged at the other axial end.

[0014] A positive electrode current collector 6 is connected to the lamination portion of the positive electrode core exposed portion 4 of the positive electrode, and a negative electrode current collector 8 is connected to the lamination portion of the negative electrode core exposed portion 5 of the negative electrode. The positive electrode current collector 6 is preferably made of aluminum or an aluminum alloy. The negative electrode current collector 8 is preferably made of copper or a copper alloy. The positive electrode terminal 7 has a positive electrode external conductive portion 13 arranged on the battery exterior side of the sealing plate 2, a positive electrode bolt portion 14 connected to the positive electrode external conductive portion 13, and a positive electrode insertion portion 15 inserted into a through hole provided in the sealing plate 2, and is electrically connected to the positive electrode current collector 6. The negative electrode terminal 9 has a negative electrode external conductive portion 16 arranged on the battery exterior side of the sealing plate 2, a negative electrode bolt portion 17 connected to the negative electrode external conductive portion 16, and a negative electrode insertion portion 18 inserted into a through hole provided in the sealing plate 2, and is electrically connected to the negative electrode current collector 8.

[0015] The positive electrode terminal 7 and the positive electrode current collector 6 are fixed to the sealing plate 2 via an internal insulating member and an external insulating member, respectively. The internal insulating member is disposed between the sealing plate 2 and the positive electrode current collector 6, and the external insulating member is disposed between the sealing plate 2 and the positive electrode terminal 7. Similarly, the negative electrode terminal 9 and the negative electrode current collector 8 are fixed to the sealing plate 2 via an internal insulating member and an external insulating member, respectively. The internal insulating member is disposed between the sealing plate 2 and the negative electrode current collector 8, and the external insulating member is disposed between the sealing plate 2 and the negative electrode terminal 9.

[0016] The electrode body 3 is housed in the exterior body 1. The sealing plate 2 is connected to the edge of the opening of the exterior body 1 by laser welding or the like. The sealing plate 2 has an electrolyte injection hole 10, which is sealed with a sealing plug after the electrolyte is injected into the exterior body 1. The sealing plate 2 is formed with a gas exhaust valve 11 for exhausting gas when the pressure inside the battery reaches or exceeds a predetermined value.

[0017] The electrolyte is a non-aqueous electrolyte containing a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, carbonates, lactones, ethers, ketones, esters, etc. can be used as the non-aqueous solvent, and two or more of these solvents can be mixed and used. When two or more solvents are mixed and used, it is preferable to use a mixed solvent containing a cyclic carbonate and a chain carbonate. For example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used as the cyclic carbonate, and dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc. can be used as the chain carbonate. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of the above-mentioned solvent is replaced with a halogen atom such as fluorine. As the electrolyte salt, LiPF 6 , LiBF 4 , LiCF 3 SO 3etc. and mixtures thereof can be used. The amount of electrolyte salt dissolved in the non-aqueous solvent can be, for example, 0.5 to 2.0 mol / L. Also, additives such as vinylene carbonate (VC) can be added as appropriate. The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte using a gel polymer or the like.

[0018] The positive electrode, negative electrode, and separator that constitute the electrode assembly 3 will be described in detail below, in particular the positive electrode active material that constitutes the positive electrode.

[0019] [Positive electrode] The positive electrode has a positive electrode core and a positive electrode composite layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, a film with the metal disposed on the surface layer, or the like can be used. The positive electrode composite layer contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both sides of the positive electrode core except for the positive electrode core exposed portion 4. The positive electrode can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, and the like to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode composite layer on both sides of the positive electrode core.

[0020] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salt, and polyethylene oxide (PEO).

[0021] The positive electrode active material includes a lithium transition metal composite oxide having a spinel structure and a coating layer having a spinel structure provided on the surface of the lithium transition metal composite oxide. Furthermore, the coating layer contains Li and does not contain Mn. This improves the rate characteristics of the battery. It can be confirmed by X-ray diffraction (XRD) that each of the lithium transition metal composite oxide and the coating layer has a spinel structure. Hereinafter, for convenience of explanation, the lithium transition metal composite oxide having the above-mentioned coating layer is referred to as "composite oxide (Z)". The positive electrode active material may be mainly composed of the composite oxide (Z) and substantially composed of only the composite oxide (Z). The positive electrode active material may contain a composite oxide other than the composite oxide (Z) or other compounds within a range that does not impair the purpose of the present disclosure.

[0022] The composite oxide (Z) is, for example, a secondary particle formed by agglomeration of a plurality of primary particles. The particle size of the primary particles constituting the secondary particle is, for example, 0.05 μm to 1 μm. The particle size of the primary particle is measured as the diameter of the circumscribed circle in a particle image observed by a scanning electron microscope (SEM). The coating layer is present on the surface of the secondary particle of the composite oxide (Z), and may also be present on the surface of the primary particle inside the secondary particle and at the grain boundary.

[0023] The composite oxide (Z) is a particle having a volume-based median diameter (D50) of, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm, and particularly preferably 7 μm to 15 μm. D50 means a particle diameter at which the cumulative frequency is 50% from the smallest particle diameter in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction type particle size distribution measuring device (e.g., MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as a dispersion medium.

[0024] The lithium transition metal composite oxide that forms the composite oxide (Z) has the general formula Li 1+α Ni 0.5-x Mn 1.5-y M x+y O 4(where 0 ≦ α < 0.2, 0 ≦ x < 0.2, 0 ≦ y < 0.5, and M is at least one element selected from Mg, Al, Sc, Ti, Cr, V, Fe, and Co) may also be represented. The molar fraction of each element constituting the lithium transition metal composite oxide is measured by inductively coupled plasma (ICP) optical emission spectrometry.

[0025] The coating layer forming the composite oxide (Z) may contain at least one element selected from Ti, Ge, V, and Cr. By containing such an element, the coating layer has a spinel structure.

[0026] It is particularly preferable that the coating layer contains at least Ge. Since the coating layer containing Ge has a low melting point, it is easy to coat.

[0027] The lattice constant a of the coating layer may be 8.10 Å < a < 8.40 Å. The lattice constant a of the lithium transition metal composite oxide is in the vicinity of 8.17 Å. When the lattice constant a of the coating layer is within the above range, the matching between the lithium transition metal composite oxide and the coating layer is improved, and the stability of the coating layer is enhanced. The lattice constant a can be calculated from the measurement results of XRD.

[0028] In the composite oxide (Z), the lithium transition metal composite oxide may include a modified layer in which the coating layer is solid-solved. The modified layer contains Li and Mn and has a composition different from that of the lithium transition metal composite oxide excluding the modified layer. In the production of the composite oxide (Z) described later, by adjusting production conditions such as the firing temperature, the presence or absence and the thickness of the modified layer can be changed.

[0029] The molar fraction of the metal elements other than Li contained in the coating layer relative to the total number of moles of the metal elements other than Li contained in the lithium transition metal composite oxide can be 0.1% to 5%. This can improve the cycle retention rate while improving the rate characteristics. The coating layer may be formed so as to cover the entire surface of the secondary particles, or may be scattered on the particle surface. The state of the coating layer can be confirmed by SEM. The thickness of the coating layer on the surface of the lithium transition metal composite oxide may be 1 μm or less.

[0030] The composite oxide (Z) can be prepared, for example, by the following procedure. (1) A Li source such as lithium hydroxide (LiOH) is added to a composite compound (X) that does not contain Li, and the resulting mixture is fired to synthesize a lithium composite oxide (Y). An example of a composite compound is a composite oxide or hydroxide that contains Ni and Mn. (2) A Li source such as LiOH and a compound containing at least one element selected from Ti, Ge, V, and Cr are added to the composite oxide (Y) to form a precursor of a coating layer that contains Li and does not contain Mn on the surface of the composite oxide (Y), and the precursor is then calcined to synthesize the composite oxide (Z).

[0031] The firing temperature in the above step (2) is, for example, 200° C. to 1050° C. By adjusting the firing temperature, it is possible to adjust the surface coverage state and thickness of the coating layer in the lithium transition metal composite oxide.

[0032] [Negative electrode] The negative electrode has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode, a film with the metal disposed on the surface layer, or the like can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the negative electrode core exposed portion 5. The negative electrode can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core.

[0033] The negative electrode mixture layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Suitable carbon-based active materials are graphites such as natural graphite, such as flake graphite, lump graphite, and earthy graphite, and artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material may be a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material may be used in combination.

[0034] The binder contained in the negative electrode mixture layer may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode, but it is preferable to use styrene-butadiene rubber (SBR). In addition, it is preferable that the negative electrode mixture layer further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), etc. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, and PAA or a salt thereof.

[0035] [Separator] The separator is a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator is preferably made of a polyolefin such as polyethylene or polypropylene, or cellulose. The separator may have either a single-layer structure or a laminated structure. A heat-resistant layer or the like may be formed on the surface of the separator.

[0036] <Example> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.

[0037] <Example 1> [Synthesis of positive electrode active material] Obtained by coprecipitation, D50 is 12μm and composition is Ni 0.5 Mn 1.5 (OH) 4The nickel manganese composite hydroxide was calcined at 500° C. to obtain a nickel manganese composite oxide (X).

[0038] Next, LiOH and nickel manganese composite oxide (X) were mixed so that the total molar ratio of Li, Ni, and Mn was 1:2. This mixture was fired at 900°C for 10 hours and then pulverized to obtain lithium composite oxide (Y). XRD confirmed that lithium composite oxide (Y) had a spinel structure. In addition, the composition of lithium composite oxide (Y) was analyzed by ICP, and the results were LiNi 0.5 Mn 1.5 O 4 It was.

[0039] In addition, the coating material (A) was prepared as the coating layer material. LiOH, Ni(OH) 2 , and GeO 2 These were mixed so that the molar ratio of Li, Ni, and Ge was 2:1:3. This mixture was fired at 900°C for 10 hours and then pulverized to obtain the coating material lithium germanium composite oxide (A). XRD confirmed that the coating material (A) had a spinel structure. The lattice constant a of the coating material (A) was 8.180 Å.

[0040] Next, this coating material (A) was pulverized in a ball mill at 300 rpm for 10 hours, and dry-mixed so that the molar ratio of the total amount of Ni and Mn in the lithium composite oxide (Y) to the total amount of Ni and Ge in the coating material (A) was 1:0.01. This mixture was heat-treated at 1,020°C in air for 30 minutes and then pulverized to form LiNi on the surface of the lithium composite oxide (Y). 0.5 Ge 1.5 O 4 As a result, a positive electrode active material coated with the above as a coating layer was obtained.

[0041] [Preparation of positive electrode] The positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 96.3:2.5:1.2, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, followed by kneading to prepare a positive electrode composite slurry. The positive electrode composite slurry was applied to both sides of a positive electrode core made of aluminum foil, and the coating was dried. The coating was then rolled using a roller and cut to a predetermined electrode size to obtain a positive electrode in which a positive electrode composite layer was formed on both sides of the positive electrode core. An exposed portion was provided in part of the positive electrode, exposing the surface of the positive electrode core.

[0042] [Preparation of negative electrode] Natural graphite was used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode composite slurry. The negative electrode composite slurry was applied to both sides of a negative electrode core made of copper foil, and the coating film was dried. The coating film was then rolled using a roller and cut to a predetermined electrode size to obtain a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode core. An exposed portion was provided in part of the negative electrode, where the surface of the negative electrode core was exposed.

[0043] [Preparation of non-aqueous electrolyte] Lithium hexafluorophosphate (LiPF 6 ) was dissolved in the mixed solvent at a concentration of 1.0 mol / L. Furthermore, vinylene carbonate (VC) was dissolved in the mixed solvent at a concentration of 2.0 mass % to prepare a non-aqueous electrolyte.

[0044] [Battery construction] An aluminum lead was attached to the exposed part of the positive electrode, and a nickel lead was attached to the exposed part of the negative electrode, and the positive and negative electrodes were spirally wound with a polyolefin separator interposed therebetween, and then pressed in the radial direction to produce a flat wound electrode body. This electrode body was housed in an exterior body made of an aluminum laminate sheet, and the nonaqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a nonaqueous electrolyte secondary battery with a design capacity of 650 mAh.

[0045] <Example 2> In preparing the coating material (A), LiOH, Co 3 O 4 , and GeO 2 A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the molar ratio of Li, Co, and Ge was 2:1:3. It was confirmed by XRD that the coating layer had a spinel structure. The lattice constant a of the coating layer was 8.196.

[0046] <Example 3> In preparing the coating material (A), LiOH, ZnO, and GeO 2 A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the molar ratio of Li, Zn, and Ge was 2:1:3. It was confirmed by XRD that the coating layer had a spinel structure. The lattice constant a of the coating layer was 8.210.

[0047] <Example 4> In preparing the coating material (A), LiOH, Co 3 O 4 , and GeO 2 A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the above materials were mixed so that the molar ratio of Li, Co, and Ge was 2:1:3, and further, the total amount of Ni and Mn in the lithium composite oxide (Y) and the total amount of Co and Ge in the coating material (A) were dry mixed so that the molar ratio was 1:0.10. It was confirmed by XRD that the coating layer had a spinel structure. The lattice constant a of the coating layer was 8.196.

[0048] <Comparative Example 1> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that no coating layer was applied and the lithium composite oxide (Y) was used as it was as the positive electrode active material.

[0049] <Comparative Example 2> Lithium composite oxide (Y) and Co 3 O 4 The total amount of Ni and Mn in the lithium composite oxide (Y) and Co 3 (OH) 4 The molar ratio of Co in the mixture was 1:0.025, and the mixture was dry mixed to form a lithium composite oxide (Y) surface. 3 O 4 A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that a positive electrode active material coated with ZnO as a coating layer was obtained. It was confirmed by XRD that the coating layer had a spinel structure. The lattice constant a of the coating layer was 8.084.

[0050] The rate characteristics and capacity retention rate after cycle testing were evaluated for each battery of the examples and comparative examples. The evaluation results are shown in Table 1. Table 1 also shows the composition of the coating layer and the molar fraction of the metal elements other than Li contained in the coating layer relative to the total number of moles of the metal elements other than Li contained in the lithium transition metal composite oxide (referred to as the "molar fraction of the coating layer" in Table 1).

[0051] [Evaluation of rate characteristics] Each battery of the examples and comparative examples was charged at a constant current of 0.5 It in a temperature environment of 25°C until the battery voltage reached 4.9 V, and then constant voltage charging was performed until the current value reached 0.02 It at 4.9 V. The battery was then left for 15 minutes. Next, constant current discharging was performed at 0.05 It until the battery voltage reached 3.0 V, and the discharge capacity C1 at 0.05 It was measured. Next, constant voltage charging was performed at 4.9 V until the current value reached 0.02 It, and the battery was then left for 15 minutes. Then, constant current discharging was performed at 0.2 It until the battery voltage reached 3.0 V, and the discharge capacity C2 at 0.2 It was measured. The rate characteristics were calculated from the following formula.

[0052] Rate characteristic (%) = C2 / C1 x 100 [Evaluation of capacity retention rate after cycle testing] The following cycle test was carried out for each battery of the Examples and Comparative Examples. The discharge capacity at the first cycle and the discharge capacity at the tenth cycle of the cycle test were determined, and the capacity retention rate was calculated by the following formula.

[0053] Capacity retention rate (%) = (10th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100 <Cycle test> The test cell was charged at a constant current of 0.5 It in a temperature environment of 25°C until the battery voltage reached 4.9 V, and then charged at a constant voltage of 0.02 It at 4.9 V. It was then discharged at a constant current of 1 It until the battery voltage reached 3.0 V. This charge / discharge cycle was repeated 10 times.

[0054] [Table 1]

[0055] As shown in Table 1, all of the batteries of the Examples had higher rate characteristics than the batteries of the Comparative Examples. In particular, in Examples 1 to 3, in which the molar fraction of the metal elements excluding Li contained in the coating layer was 1% relative to the total number of moles of the metal elements excluding Li contained in the lithium transition metal composite oxide, it was possible to improve the cycle retention rate while improving the rate characteristics, compared to Comparative Example 1, which had no coating layer. [Explanation of symbols]

[0056] 1 Exterior body 2 Sealing plate 3 Electrode body 4 Positive electrode core exposed part 5 Negative electrode core exposed part 6 Positive electrode current collector 7 Positive terminal 8 Negative electrode current collector 9 Negative terminal 10 Electrolyte injection hole 11 Gas exhaust valve 13 Positive electrode outer conductive part 14 Positive Bolt Part 15 Positive electrode insertion part 16 Negative electrode outer conductive part 17 Negative Bolt Part 18 Negative electrode insertion part 100 Secondary battery

Claims

1. A lithium transition metal composite oxide containing Li, Ni, and Mn and having a spinel structure; a coating layer having a spinel structure, which contains Li and does not contain Mn and is provided on a surface of the lithium transition metal composite oxide; The coating layer comprises at least Ge.

2. The lithium transition metal composite oxide has the general formula Li 1+α Ni 0.5-x Mn 1.5-y M x+y O 4 2. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, represented by the formula: (wherein 0≦α<0.2, 0≦x<0.2, 0≦y<0.5, and M is at least one element selected from the group consisting of Mg, Al, Sc, Ti, Cr, V, Fe, and Co).

3. 3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lattice constant a of the coating layer is in the range of 8.10 Å<a<8.40 Å.

4. 4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal composite oxide includes an altered layer in which the coating layer is dissolved in solid form.

5. 5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein a molar fraction of the metal elements excluding Li contained in the coating layer relative to a total mole number of the metal elements excluding Li contained in the lithium transition metal composite oxide is 0.1% to 5%.

6. A positive electrode comprising the positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5; A negative electrode; An electrolyte.

Citation Information

Patent Citations

  • Anode active material for lithium secondary batteries having a core-shell layer structure, method for manufacturing the same, and lithium secondary battery using the same

    JP2008535173A

  • Electrode active material, method of producing the same and electrode adopting the same, and lithium battery

    JP2012234818A

  • Nonaqueous electrolyte secondary battery

    JP2016031852A